PREFERENSI KONSUMEN TERHADAP BIHUN DI KOTA BANDAR LAMPUNG DAN METRO - Sayekti, Wuryaningsih Dwi (Indonesian Journal of Socio Economics)
The objective of this research was to know consumerâs preference at the city of Bandar Lampung and Metro. Data were collected on September until November 2006. Survey and census method were aplied for this research and used simple cluster sampling and sequential sampling technic. Data were analyzed by Conjoint Analysist. The result showed that the colour and package size of vermicelli were be two highest importance atribute. In general the atributes of vermicelli which had tend to be more prefered by consumer were white colour, not sting flavor, little diameter, cheap price, not rubbery, and silk-screening merk. Vendor consumer at Bandar Lampung like vermicelli which have atributes: white colour, price per 100 gramÂ  more than Rp1.200,00, rubbery texture, poured packaging,Â  not sting flavor, the size of package more than 0,5 kg, little diameter, and silk-screening merk. Vendor consumer at Metro like vermicelli which have atributes: transparent colour, price per 100 gram less than Rp1.200,00, rubbery texture, poured package,Â  sting flavor, the size of package more than 0,5 kg, little diameter, and not silk-screening merk. Household cosumers at Bandar Lampung like vermicelli which have atributes: white colour, price per 100 gram less than Rp1.200,00, rubbery texture, packaged,Â  not sting flavor, the size of package 0,25-0,5 kg, little diameter, and silk-screening merk.Â  Household consumers at Metro like vermicelli which have atributes: transparent colour, price per 100 gram less than Rp1.200,00, not rubbery texture, packaged,Â  not sting flavor, the size of package less than 0,25kg, little diameter, and silk-screening merk.